Numerical Computation of Vehicle Wading. A Study Using the VOF Method. - Varnousfaderani, Shayan Rahat (My University, 2013)
A method was developed for the numerical calculation of vehicle wading in the commercial software Fluent. The VOF method was used for modeling of the two-phase flow. This method combines the two phases, air and water, into a single fluid with variable properties. The results were examined to gain a better understanding of the characteristics of the velocity field and the variation of the wading-line height on the car. The results show qualitative agreement with tests carried out at the Hällered test facility. Comprehensive quantitative comparisons were not attempted as measurement of the relevant variables requires upgrading of the testing equipment available. A simplified procedure was also developed for estimating the vertical force on the car and the subsequent height raise. The method neglects dynamic effects and was found to overestimate the force. Yet, the method is useful as a dynamic balance calculation is not currently feasible. Suggestions for improving wading performance evaluation are provided that can build on the work done during this project.
Keywords: Transport; Hållbar utveckling; Strömningsmekanik; Transport; Sustainable Development; Fluid mechanics